Islam Between Structure and Agent Duality in Maryam: Anthony Giddens’ Perspective of Novel by Okky Madasari - Dharma, Laga Adhi (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
Conflicts with religious backgrounds are a phenomenon that often occurs unexpectedly around us. These events can inspire authors to write into the literary works that they produce. Social conditions cannot be separated from the process of the birth of a literary work. This paper aims to describe the social structure that influences the author in writing a literary work, as well as how the author tries to build a narrative to influence the social structure through his work. The formulation of the research problem is related to whether the social structure affects the agent (author) and how the agent (author) represents what is in Maryam's novel. The theory used in this research is the structuration concept proposed by Anthony Giddens. The results showed that the social structure, especially about the Ahmadiyah conflict on the island of Lombok, influenced Okky Madasari as an author (agent) in producing the novel Maryam. There are also ideas developed by Okky Madasari which aim to influence the social structure through his work. This is where the duality process between social structures and agents influences one another.